Software process improvement and capability determination 11th International Conference, SPICE 2011, Dublin, Ireland, May 30 - June 1, 2011, Proceedings - O'Connor, Rory V. (Berlin, Heidelberg Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the 11th International Conference on Software Process Improvement and Capability Determination, SPICE 2011, held in Dublin, Ireland, in May/June 2011. The 15 revised full papers presented and 15 short papers were carefully reviewed and selected from numerous submissions. The papers are organized in topical sections on process modelling and assessment, safety and security, medi SPICE, high maturity, implementation and improvement.
Keywords: Software engineering -- Congresses; Computer software -- Congresses; Electronic books